Whistler mode propagation through weakly ionized magnetoplasma - Singh R.N. (My University, 2025)
The VLF wave generation by Čerenkov process from weakly ionized plasma has been considered. The effect of collisions on Čerenkov power spectrum and on propagation of VLF waves in whistler mode has been studied. The radiated power is shown to depend on the collisional parameter. The presence of collisions is found to modify the refractive index surfaces. It is shown that the focussing of VLF waves is less probable in the presence of collisions. © 1974.